ANALYZE INFLUENCE OF MODERN INFORMATION TECHNOLOGY ON PUPIL’S EYESIGHT AND HEARING (Experimental biology, 2016)
XXI century is giving much “technology marvel” such as computer and world information net Internet. Nowadays there are many arguments among studied people about beneficial and harmful effects of modern technology on health. Modern technology such as computer has harmful effects on physical, psychologic health and eyesight, hearing.When people read a book the light reflect on paper. However, the computer is source of light. That’s why eyes of people are tired from light.Nowadays many people listen to music by headphone and radio. Researchers notice that people who listen to music by headphone have dizziness, noise in ears. When we suddenly increase the voice of music to high while listening, ear of person will deafness. Because people can listen to 16-20000hertz frequency. If people listen to music frequency 90decibel, their ability of ear will decrease. The frequency of music, radio, music by headphone is 110decibel.
Keywords: sight analyzers; hearing analyzers; deterioration a vreziya of eyes; hearing deterioration; a syndrome of computer vision; a syndrome сухлсти an eye; a miopiya.